The role of the coach - Feher, T. (EWF Symposium, Verona, Italy, March 27, 2010, 2010)
Powerpoint-Präsentation auf dem Seminar des Europäischen Gewichtheberverbands 2010 in Verona. Der Autor stellt seine Grundauffassung zum Trainerberuf vor. Diese lautet: The coach - forms, develops and exerts positive influence on athlete`s: - general and specific physical capabilities - psychological capabilities - mental capabilities - lays down the foundations of a future sport career - forms and develops the athlete`s personality - prepares the athlete to the challenges of life.